The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1590/s0100-879x1999000100014
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of rats exposed to fluoxetine or venlafaxine during the third week of pregnancy

Abstract: The aim of the present study was to compare the toxic effects of fluoxetine (F) (8 and 16 mg/kg) and venlafaxine (V) (40 and 80 mg/kg) administered during the third week of pregnancy on early development of rats. Both antidepressants were administered by gavage on pregnancy days 15 to 20 to groups of 10 to 12 animals each. Duration of gestation, food and water consumption, number of live pups and birth weight were recorded. Litters were culled to six pups at birth (day 1) and followed for growth until weaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 11 publications
6
36
1
Order By: Relevance
“…Similar results have been reported in other studies with rodents [43][44][45][46][47][48][49][50]. In addition to low birth weight due to prenatal SSRIs, da-Silva et al also found a sex and treatment effect, females with SSRI exposure had lower birth weight than males and nonexposed females [47].…”
Section: Animal Studies (Seesupporting
confidence: 85%
“…Similar results have been reported in other studies with rodents [43][44][45][46][47][48][49][50]. In addition to low birth weight due to prenatal SSRIs, da-Silva et al also found a sex and treatment effect, females with SSRI exposure had lower birth weight than males and nonexposed females [47].…”
Section: Animal Studies (Seesupporting
confidence: 85%
“…9 In humans, the teratogenic potential of most therapeutic agents remains unknown and is rarely related to specific malformations. It is estimated that 10% of congenital malformations are attributed to environmental causes, including the use of medication, while 21% occur due to either genetic or chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were then separated into three groups (n = 5 each) and treated intraperitoneally with 10mg/kg/ day 7 of the test substances on the ninth, tenth and eleventh day The administration of 10mg/kg/day is equivalent to the dose used for treating anxiety-related disorders, 7 although other studies have reported that fluoxetine has been prescribed at doses ranging from 8mg to 16mg/kg/day. 9 On the twenty-first day of pregnancy, the rats were weighed and anesthetized intraperitoneally with xilazine (Rompum® 20mg/ mL, Bayer) and ketamine hydrochloride (Ketamin-S(+)® 50mg/ mL, Cristália) at a ratio of 1:3 at a dose of 0.3mL for each 100g of animal weight. Through a long abdominal incision, the fetuses were exposed and distributed into 3 groups: 55 in the control group, 62 in the fluoxetine group and 57 in the imipramine hydrochloride group.…”
Section: Methodsmentioning
confidence: 99%
“…Few investigations have also focused on the behavioral consequences of perinatal treatment with the novel antidepressants, such as venlafaxine, mirtazapine, reboxetine, nefazodone, and milnacipran. A recent report found no detrimental effects in rats gestationally exposed to venlafaxine (da Silva et al, 1999). There are no published reports showing neurochemical and behavioral effects induced by perinatal administration of novel antidepressants.…”
Section: Novel Antidepressantsmentioning
confidence: 95%